Remains of Leatherback turtles, Dermochelys coriacea, at Mid-Late Holocene archaeological sites in coastal Oman: clues of past worlds - John G. Frazier; Valentina Azzarà; Olivia Munoz; Lapo Gianni Marcucci; Emilie Badel; Francesco Genchi; Maurizio Cattani; Maurizio Tosi; Massimo Delfino (PeerJ, 2018)
Small, irregular isolated bones identified as remains of leatherback turtles (Dermochelys coriacea) were recovered from Mid to Late Holocene sites at Ra’s al-Hamra and Ra’s al-Hadd, coastal Oman. These provide the third instance of this animal being documented from any prehistoric site anywhere, and the records provide one of the oldest, if not the oldest, dates for this distinctive chelonian—even though they do not refer to fossils. Decades of research in this region has yielded vast amounts of archeological information, including abundant evidence of intense exploitation and utilization of marine turtles from about 6,500 to 4,000 BP. During part of this period, turtle remains in human burials have been extraordinary; the turtle involved, Chelonia mydas, has been abundant in the region during modern times. Yet despite intense and varied forms of prehistoric marine resource exploitation, and major, long-term archeological work, no other turtle species has been previously authenticated from these, or other coastal sites. The documentation of remains of the largest and most distinctive of living marine turtles, D. coriacea, at Ra’s al-Hamra and Ra’s al-Hadd, presented herein, provide detailed information that serves as the basis for future interpretations and discussions regarding incomplete, disarticulated remains from the Mid to Late Holocene, particularly in reference to taphonomic questions and diverse environmental conditions.